Understanding English teachers' non-volitional use of online teaching: A Chinese study. (October 2021) - Huang, Fang; Teo, Timothy; Guo, Jiayi
Abstract: This study investigated factors influenced Chinese English as a foreign language (EFL) teachers' non-volitional online teaching intentions based on an extended technology acceptance model (TAM). Facilitating conditions, technology complexity, and perceived anxiety were added to the original TAM as extended variables to examine their influence on Chinese EFL teachers' online teaching. Quantitative data were obtained from 158 teachers in Chinese primary and secondary schools and universities. Data were analyzed using structural equation modeling (SEM), and the extended TAM was found to be valid in explaining Chinese EFL teachers' online teaching intentions during quarantine. Teachers' behavioral intentions were significantly associated with their attitudes and perceived usefulness of online teaching. Their perceptions of ease of use significantly influenced usefulness, which was significantly associated with teachers' attitudes. Facilitating conditions have been suggested as an important antecedent to ease of use. Suggestions were provided for teachers and educational administrators to revisit the affordances of online teaching with the aim of coping with emergencies.